Pengembangan Bahan Ajar Konsep Dasar Fisika SD Berbasis Model Pembelajaran Project Based Learning Untuk Meningkatkan Keterlibatan Mahasiswa Umuslim Bireun - Novi Sari Liani; Ayunda, Desy Sary; Intan Wulan Sari; Elisyah, Nur (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
This study aims to develop teaching materials for basic concepts of elementary physics based on the project-based learning model to increase the involvement of Umuslim Bireun students and test feasibility. The type of research used in this research is a type of quantitative research with the Research and Development (R&D) research method. With the ADDIE development model used analysis, design, development, implementation and evaluation. The research results of the media expert validation results show that it is brought to the media aspect, technical quality and media size with a presentation value of 80.22%, 87.15%, 90.42% so that it is concluded to be very good. The results of the material expert analysis clearly show that the material coverage, material accuracy, accuracy and stimulate desire, media presentation with presentation values of 88.36%, 87.24%, 92.82%, 90.44%, 92.41% so that it is concluded to be very good. The overall feasibility test results of individual, group and field validation with a percentage of 89%, 88% and 87% qualifications are very feasible. The results of the gain normality test analysis obtained the results of 0.92 so that it can be concluded that there is an increase in the involvement of Umuslim students with teaching materials for basic elementary physics concepts based on the project-based learning model.